Integrative transcriptome analysis reveals TEKT2 and PIAS2 involvement in diabetic nephropathy. Issue 11 (17th October 2022) - Li, Yuanqing; Lin, Hongchun; Shu, Shuangshuang; Sun, Yuxiang; Lai, Weiyan; Chen, Wenfang; Hu, Zhaoyong; Peng, Hui
Abstract: Cell heterogeneity has impeded the accurate interpretation of the bulk transcriptome data from patients with diabetic nephropathy (DN). We performed an analysis by integrating bulk and single‐cell transcriptome datasets to uncover novel mechanisms leading to DN, especially in the podocytes. Microdissected glomeruli and tubules transcriptome datasets were selected from Gene Expression Omnibus (GEO). Then the consistency between datasets was evaluated. The analysis of the bulk dataset and single‐nucleus RNA dataset was integrated to reveal the cell type‐specific responses to DN. The candidate genes were validated in kidney tissues from DN patients and diabetic mice. We compared 4 glomerular and 4 tubular datasets and found considerable discrepancies among datasets regarding the deferentially expressed genes (DEGs), involved signaling pathways, and the hallmark enrichment profiles. Deconvolution of the bulk data revealed that the variations in cell‐type proportion contributed greatly to this discrepancy. The integrative analysis uncovered that the dysregulation of spermatogenesis‐related genes, including TEKT2 and PIAS2, was involved in the development of DN. Importantly, the mRNA level of TEKT2 was negatively correlated with the mRNA levels of NPHS1 ( r = −.66, p < .0001) and NPHS2 ( r = −.85, p < .0001) in human diabetic glomeruli. Immunostaining confirmed that the expression of TEKT2 and PIAS2 were up‐regulated in podocytes of DN patients and diabetic mice. Knocking down TEKT2 resisted high glucose‐induced cytoskeletal remodeling and down‐regulation of NPHS1 protein in the cultured podocyte. In conclusion, the integrative strategy can help us efficiently use the publicly available transcriptomics resources. Using this approach and combining it with classical research methods, we identified TEKT2 and PIAS2, two spermatogenesis‐related genes involved in the pathogenesis of DN. Furthermore, TEKT2 is involved in this pathogenesis by regulating the podocyte cytoskeleton.